(untitled) (JURNAL ULET (Utility, Earning and Tax), 2024)
The purpose of this study is to determine the financial performance of the Rezky Furniture Business by using financial ratio measuring tools in the form of profitability ratios and activity ratios. The method used is a descriptive method. Data collection techniques that was used were interview and documentation techniques. The data analysis carried out was an analysis of the financial reports of the Rezky Furniture Business for three periods using financial ratios. Based on the research results, it was concluded that in the aspect of making a profit, Rezky’s Furniture Business has good financial performance and in the aspect of using its assets, Rezky’s Furniture Business has good performance